2023
DOI: 10.3390/biom13091314
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis Guides Transporter Protein Deorphanization: A Case Study of the SLC25 Family of Mitochondrial Metabolite Transporters

Katie L. Byrne,
Richard V. Szeligowski,
Hongying Shen

Abstract: Homology search and phylogenetic analysis have commonly been used to annotate gene function, although they are prone to error. We hypothesize that the power of homology search in functional annotation depends on the coupling of sequence variation to functional diversification, and we herein focus on the SoLute Carrier (SLC25) family of mitochondrial metabolite transporters to survey this coupling in a family-wide manner. The SLC25 family is the largest family of mitochondrial metabolite transporters in eukaryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…To explore the regulatory mechanism of A39, we performed amino acid sequence analysis 14,16 and Alphafold structure prediction 17 of A39. In addition to the typical structural fold, the threefold pseudo-symmetrical, six transmembrane α-helices surrounding the central transport cavity, the analysis revealed that A39 contains an extra mitochondrial matrix loop between transmembrane domain 1 and 2 with a low structural prediction confidence score (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To explore the regulatory mechanism of A39, we performed amino acid sequence analysis 14,16 and Alphafold structure prediction 17 of A39. In addition to the typical structural fold, the threefold pseudo-symmetrical, six transmembrane α-helices surrounding the central transport cavity, the analysis revealed that A39 contains an extra mitochondrial matrix loop between transmembrane domain 1 and 2 with a low structural prediction confidence score (Fig.…”
Section: Resultsmentioning
confidence: 99%